Ensuring the Safety of Wheeled Transport Vehicles When Driving in Fog Conditions - Bobur Ikromov (Genius Journals, 2023)
When driving a car in fog conditions, the driver's vision decreases, which means that driving the car as slowly as possible and being careful is required. Fog causes negative emotions, under its influence, the driver experiences fear and impaired vision
Keywords: fog; fog lights; road covered with fog, car; types of fog, international requirements